2023
DOI: 10.26508/lsa.202302279
|View full text |Cite
|
Sign up to set email alerts
|

Decline of DNA damage response along with myogenic differentiation

Haser H Sutcu,
Phoebe Rassinoux,
Lise-Marie Donnio
et al.

Abstract: DNA integrity is incessantly confronted to agents inducing DNA lesions. All organisms are equipped with a network of DNA damage response mechanisms that will repair DNA lesions and restore proper cellular activities. Despite DNA repair mechanisms have been revealed in replicating cells, still little is known about how DNA lesions are repaired in postmitotic cells. Muscle fibers are highly specialized postmitotic cells organized in syncytia and they are vulnerable to age-related degeneration and atrophy after r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 82 publications
6
10
0
Order By: Relevance
“…1, A and C vs Fig. S1, A and C), as we previously reported (33). Likewise, we observed that this was also the case upon 10,000 protons irradiation (Fig.…”
Section: The Dynamic Behavior Of Ku80-gfp At the Dna Damage Site Depe...supporting
confidence: 89%
See 4 more Smart Citations
“…1, A and C vs Fig. S1, A and C), as we previously reported (33). Likewise, we observed that this was also the case upon 10,000 protons irradiation (Fig.…”
Section: The Dynamic Behavior Of Ku80-gfp At the Dna Damage Site Depe...supporting
confidence: 89%
“…Thereby, we demonstrated that DSB repair (DSBR) mechanisms in proliferating myogenic cells, myoblasts, switch as a function of energy deposition and time after irradiation, whatever the particle delivered, proton or α-particle. Additionally, we found that myoblasts orchestrate IR-induced DSB repair with dynamics that depend on the type of high LET particle used, proton or α-particle, while differentiated myotubes remained with declined DNA damage response as was previously reported (33).…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations